2019
DOI: 10.3390/app9183687
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Venturi Structures on the Cleaning Performance of a Pulse Jet Baghouse

Abstract: In order to study the effect of venturi structures on the cleaning performance of a pulse jet baghouse, several cleaning tests are carried out applying the pulse jet test bench. Experiments are performed using different filter bags with venturi tubes of varying throat diameters and lengths. Peak pressure and peak pressure arrival time are selected to evaluate the cleaning efficiency under different conditions. On this basis, a series of comparative experiments are conducted between a typical venturi-type and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In this study, we did not deeply analyse the influence of the vortex on the internal flow field and fertilizer injection performance of the Venturi injector. Liu and Shen (2019) showed that when vortex and turbulence appeared in the throat, the negative pressure value fluctuated. According to Figure 8, setting the diffusion section as an arc structure could make the vortex area unable to form at the throat and reduce the influence of the vortex on the negative pressure of the throat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we did not deeply analyse the influence of the vortex on the internal flow field and fertilizer injection performance of the Venturi injector. Liu and Shen (2019) showed that when vortex and turbulence appeared in the throat, the negative pressure value fluctuated. According to Figure 8, setting the diffusion section as an arc structure could make the vortex area unable to form at the throat and reduce the influence of the vortex on the negative pressure of the throat.…”
Section: Discussionmentioning
confidence: 99%
“…According to Figure 8, setting the diffusion section as an arc structure could make the vortex area unable to form at the throat and reduce the influence of the vortex on the negative pressure of the throat. There are many ways to reduce the vortex, such as adopting the segmented diffusion section (Liu & Shen, 2019). We only compared and analysed the difference in fertilizer injection performance between the linear diffusion section and the arc diffusion section.…”
Section: Discussionmentioning
confidence: 99%
“…Pulverized coal filters are usually in the form of bag filters, which are currently a relatively effective technical device for managing air pollution. Metal fiber filter bags are a new type of filter used in chemical, metallurgical, petroleum, and environmental protection applications to intercept solid contaminants in fluids [4]. Compared with a traditional cloth filter bag, which has high-temperature resistance, corrosion resistance, processability, a long service life, and other beneficial characteristics, metal bags can be a good solution to the harsh working conditions that occur under the conditions of paste films, bags being burned by high temperatures, or broken filter bags resulting in dust leakage and other problems, effectively reducing the production costs of enterprises and improving the production capacity of equipment [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous studies attempting to understand the mechanism of filter bag cleaning and optimize the parameters of a bag cleaning system to enhance the cleaning performance [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Qian et al investigated the optimal relationship of nozzle diameter with jet distance and blow tube size, while Shim et al and Andersen et al developed novel configurations of pulse-jet nozzles and examined them through experimental and computational methods [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Qian et al investigated the optimal relationship of nozzle diameter with jet distance and blow tube size, while Shim et al and Andersen et al developed novel configurations of pulse-jet nozzles and examined them through experimental and computational methods [7][8][9][10]. Additionally, other operational parameters such as initial tank pressure [5][6][7]11,[13][14][15]18], pulse-jet duration [5][6][7]17], induced airflow [5,7,14,16], and surface treatment [12,14,17] have been discussed.…”
Section: Introductionmentioning
confidence: 99%